Workshop on the Double-Edged Sword of Artificial Intelligence: A Study on the Effectiveness of Outreach for Mitigating the Risk of AI Crime - Lubis, Muharman; Thamrin, Daffa Shidqi (Universitas Syiah Kuala, 2025)
Artificial Intelligence (AI) is a double-edged sword that offers innovation as well as advanced new cyber threats, known as AI Crime. The purpose of this activity is to measure and evaluate the effectiveness of outreach in improving cyber literacy among webinar participants regarding the classification, risks, and mitigation strategies of AI Crime. The outreach was conducted on Sunday, October 5, 2025, via Zoom and was attended by 92 participants. Quantitative data was collected through pre-tests and post-tests. The community service focused on presenting AI as a double-edged sword in technological advancement, which can lead to violations divided into three types of AI Crime threats (with, on, and by AI). The average pre-test score was 94.78%. This score increased to 95.22% on the post-test, resulting in an effectiveness improvement of 0.46%. This high initial score indicates a ceiling effect. This small but positive improvement confirms the success of socialization in strengthening public knowledge. Qualitative findings also show that participants need guidance in detecting deepfakes and data privacy protection strategies. Regarding deepfake detection itself, several studies also describe ways to deal with it, which are by using AI technology and other technologies such as blockchain. In this era of AI advancement, data privacy protection strategies require appropriate regulations, which require cooperation between stakeholders regarding the duality of AI use. Not only that, but we as end-users of technology must also participate in realizing justice in the use of technology by increasing digital literacy regarding AI advances, one of which is through this community service webinar. This research emphasizes the important role of public education as a crucial risk mitigation measure for AI use in this era of smart technology.